Challenges and Strategies in Navigating the TOEFL Reading Section Among Selected Indonesian EFL Learners - Nursalim, Nursalim; Ajam , Ali; Rizal , Awaludin; Lengkoan , Fergina; Budiman , Jeihn N. C. (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
In an era where English proficiency dictates global academic and professional mobility, mastering the TOEFL Reading section remains a significant hurdle for many Indonesian EFL learners. Despite familiarity with widely endorsed strategies such as skimming, scanning, and vocabulary enhancement, consistent application under exam pressure remains elusive. This study addresses a critical gap in existing research by investigating not only the types of challenges faced by TOEFL takers but also the cognitive and strategic dissonances that hinder their performance. Employing a mixed-methods approach, the study collected quantitative data from the reading scores of 15 test-takers at an English Language Center in Tondano, North Sulawesi, and complemented it with qualitative insights from semi-structured interviews. The findings reveal persistent difficulties in time management, complex vocabulary processing, and inference-based questions, despite students’ awareness of effective strategies. Notably, the study uncovers that the mere knowledge of techniques is insufficient without strategic internalization, adaptive focus, and real-time cognitive flexibility. Students identified vocabulary expansion, active reading, and timed practice as the most impactful strategies, yet gaps between awareness and execution remain. The study’s contribution lies in offering a nuanced understanding of these strategic breakdowns and advocating for targeted pedagogical interventions, including strategy-focused curricula and individualized practice modules. These findings hold wider implications for TOEFL preparation programs, suggesting the need for personalized, cognition-aware teaching models that not only transmit strategies but also cultivate their consistent application in high-stakes contexts.